HPV prevalence and genotype distribution in 2,306 patients with cervical squamous cell carcinoma in central and eastern China - Chunrong Han; Wanqiu Huang; Mei Ye; Rong Zou; Jianyun Lan; Jing Chen; Jingui Jiang; Hongjing Wang; Lin Xia; Jun Luo; Dongbin Li; Jianxiang Geng; et al. (Frontiers in Public Health, 2023)
BackgroundTo explore the positivity rate and genotype distribution of human papillomavirus (HPV) in cervical squamous cell carcinoma (CSCC) tissues in central and eastern China and to provide theoretical basis for cervical cancer screening and prophylactic HPV vaccine development in China.MethodsDNA was extracted from paraffin-embedded tissues of CSCC samples and exfoliated cervical cells of cervical cancer screening populations. 23 HPV genotypes were detected by combining polymerase chain reaction (PCR) and reverse dot hybridized gene chip detection technology in 2,306 CSCC tissues and 10,245 cervical cancer screening populations. The genotype distribution of HPV infection was analyzed.ResultsThe overall infection rate of HPVs in 2,306 CSCC patients was 92.71%. The frequency of single-type HPV infection and multiple-type HPV infection were 86.48% and 13.51%, respectively. The most common HPV genotypes detected in Chinese CSCC tissues were HPV-16, HPV-18, HPV-31, HPV-33, HPV-45, HPV-52, HPV-58, and HPV-59. The overall positivity rate of these eight high-risk HPV (HR-HPV) genotypes in HPV-positive CSCC was as high as 96.91%. Of which the positivity rate of seven HR-HPV genotypes related to nine-valent HPV vaccines in HPV-positive CSCC was 95.09%. Meanwhile, the overall infection rates of HR-HPV and low-risk HPV (LR-HPV) in female aged 35–64 years who underwent cervical cancer screening were 13.16% and 1.32%, respectively. The high-frequency HR-HPV genotypes in cervical cancer screening women were HPV-52, HPV-58, HPV-16, HPV-53, HPV-68, HPV-39, HPV-51, and HPV-56, with positivity rates of 2.25%, 1.60%, 1.31%, 1.22%, 0.93%, 0.92%, 0.78%, and 0.74%, respectively.ConclusionAmong women screened for cervical cancer in China, detecting the 8 high-frequency HR-HPV genotypes can reduce technical difficulty and reagent costs, while also improving the efficiency and effectiveness of cervical cancer screening. HPV genotyping assists gynecologists in assessing the risk of HR-HPV-positive cervical intraepithelial neoplasia and guiding them in implementing appropriate interventions. Furthermore, HPV genotyping is helpful for doctors to follow up HR-HPV-positive women and to evaluate the protective effect of HPV vaccine.